Group portrait of the attendees of the August 1957 Monte Toyon Camp - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the Monte Toyon C Camp, held August 3-10, 1957 in Aptos, California.